Magnetically Induced Anisotropic Interaction in Colloidal Assembly - Fan, Qingsong; Li, Zhiwei; Wu, Chaolumen; Yin, Yadong (Precision Chemistry, 2023)
The wide accessibility to nanostructures with high uniformity and controllable sizes and morphologies provides great opportunities for creating complex superstructures with unique functionalities. Employing anisotropic nanostructures as the building blocks significantly enriches the superstructural phases, while their orientational control for obtaining long-range orders has remained a significant challenge. One solution is to introduce magnetic components into the anisotropic nanostructures to enable precise control of their orientations and positions in the superstructures by manipulating magnetic interactions. Recognizing the importance of magnetic anisotropy in colloidal assembly, we provide here an overview of magnetic field-guided self-assembly of magnetic nanoparticles with typical anisotropic shapes, including rods, cubes, plates, and peanuts. The Review starts with discussing the magnetic energy of nanoparticles, appreciating the vital roles of magneto-crystalline and shape anisotropies in determining the easy magnetization direction of the anisotropic nanostructures. It then introduces superstructures assembled from various magnetic building blocks and summarizes their unique properties and intriguing applications. It concludes with a discussion of remaining challenges and an outlook of future research opportunities that the magnetic assembly strategy may offer for colloidal assembly.